The Experiences of Motherhood among Black Undergraduate Students at a South African University: Reconciling Competing Roles. Issue 2 (3rd April 2018) - Maisela, Thato; Ross, Eleanor
ABSTRACT: While South African educational policy gives all persons the right to attend educational institutions irrespective of pregnancy or maternal status, it can be demanding to be both a student and a mother and to reconcile competing conceptions of what it means to be a "good student" and a "good mother"—particularly within African culture. The research adopted a feminist ethics of care perspective and gender role theory to explore the challenges that university-level mothers experience and the strategies they adopt to cope with their situations. The study was located within a qualitative research paradigm and involved semi-structured interviews with a purposive sample of 14 female undergraduate university students. Key findings were that the student mothers experienced financial, social and emotional challenges, but were able to cope with the support of family and friends. These findings have implications for the support and empowerment of student mothers to enable them to reconcile competing roles of student and mother.